2004
DOI: 10.1074/jbc.m404787200
|View full text |Cite
|
Sign up to set email alerts
|

The Wilms Tumor Suppressor-1 Target Gene Podocalyxin Is Transcriptionally Repressed by p53

Abstract: Wilms tumor is a pediatric kidney cancer that affects 1 in 10,000 children. The Wilms tumor suppressor-1 (WT1) 1 gene was identified as a tumor suppressor gene based upon the presence of WT1 mutations in a subset (ϳ10 -15%) of Wilms tumor samples (reviewed in Ref. 1). However, the majority of Wilms tumor cases cannot be explained by genetic alteration of the WT1 locus. There may be disruption of biological pathways either upstream or downstream of WT1, or there may be pathways independent of WT1 leading to thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 44 publications
(65 reference statements)
2
31
1
Order By: Relevance
“…The classic p53 target gene p21 was downregulated in the anaplastic Wilms tumors, indicating a deficiency in p53 activity in these tumors. Additional evidence comes from our recent work where we have demonstrated that Podocalyxin, a gene upregulated in anaplastic Wilms tumors, was transcriptionally repressed by p53 in a Wilms tumor cell line (Stanhope-Baker et al, 2004). The molecular bases underlying the anaplastic nuclear morphology remain unknown.…”
Section: An Expression Signature For Anaplastic Wilms Tumormentioning
confidence: 91%
“…The classic p53 target gene p21 was downregulated in the anaplastic Wilms tumors, indicating a deficiency in p53 activity in these tumors. Additional evidence comes from our recent work where we have demonstrated that Podocalyxin, a gene upregulated in anaplastic Wilms tumors, was transcriptionally repressed by p53 in a Wilms tumor cell line (Stanhope-Baker et al, 2004). The molecular bases underlying the anaplastic nuclear morphology remain unknown.…”
Section: An Expression Signature For Anaplastic Wilms Tumormentioning
confidence: 91%
“…It was identified as an endogenous downstream target of the WT1 TSG, mediating glomerular differentiation (Palmer et al, 2001). PODXL is a target of p53-mediated transcriptional repression in a Wilm's tumor cell line (Stanhope-Baker et al, 2004).…”
Section: Functional Characterization Of St7 Cs-f Hooi Et Almentioning
confidence: 99%
“…Unlike most of the cancers discussed in this review, PC expression (transcript) is significantly reduced in 64 patient nephroblastoma samples (relative mean 0.29) compared to pooled normal fetal kidney (Stanhope-Baker et al, 2004). Although WT1 is a positive regulator of PODXL expression (Palmer et al, 2001), and loss of WT1 expression is associated with some Wilms' tumours, there was no evidence of a correlation between PODXL and WT1 expression in this study (Stanhope-Baker et al, 2004). However, perhaps of diagnostic value, this same study showed that PODXL expression was increased in more aggressive, anaplastic tumours compared to 40 non-anaplastic tumors (StanhopeBaker et al, 2004).…”
Section: Wilms' Tumor (Nephroblastoma)mentioning
confidence: 99%
“…Notably, functional loss of p53 is associated with the most aggressive, anaplastic nephroblastomas with poor prognosis. As p53 negatively regulates PODXL expression (Stanhope-Baker et al, 2004), enhanced PODXL expression in anaplastic nephroblastomas may be explained directly by this genetic pathway. Although more study is required to know if enhanced PODXL expression in anaplastic nephroblastoma has a direct role in promoting tumour aggressiveness, expression of PODXL in nephroblastoma may be useful as a marker of poorly differentiated, anaplastic tumours.…”
Section: Wilms' Tumor (Nephroblastoma)mentioning
confidence: 99%
See 1 more Smart Citation